How Successful is the College of Nursing, Kuwait, in Reducing Dependence on Expatriates? - Al-Ali, Salah (Technium Social Sciences Journal, 2021)
Technical and vocational education is a dual system that is important for life-long learning and training and play a vital role in providing students with an opportunity for the world of work. It is completely different from formal learning and allow students to transfer what they have learned in class room into real work practice. However, technical and vocational education is experiencing a great challenge to cope with the rapid change in science and technology in industries and business. This was worsening by the social images that technical and vocational education is design for those students who come from the back gate of a university. It is highly significant to promote the role of technical and vocational education in increasing economic competitiveness and social and education inclusion. In developing countries (e.g., Kuwait, United Arab Emirates), governments have exerted efforts to enhance indigenous capabilities by forging technical and vocational education institutions. The aim is to enhance local capabilities in vital sectors (e.g., oil, electricity and water, health care), and reduce dependence on expatriates. The research paper focuses on identifying and examining the perception of students at the College of Nursing, CN, towards the quality of teaching and learning. In addition to, examining the perception of the CN graduate’s heads of nurses at the health sector towards the standard of the field training program, and the quality CN graduates. The research is based on extensive field work that encompasses a review of the related literature, questionnaires, and interviews with a sample of heads of departments at the CN. Interviews were also conducted with the heads of nurses in four major hospitals in four districts at the health sector. Finally, the research will argue that unless the CN recognize and appreciate the value of building a strong linkage with the health sector, its contribution in tackling the shortage of skilled and semi-skilled indigenous health care specialist will be below the government expectations, thus continuing relaying on expatriates for years ahead.